Multi-feature fusion energy-saving routing in internet of things based on hybrid ant colony algorithm. (30th April 2020) - Ren, Xiao-Li; Yang, Jian-Wei; Li, Nai-Qian
This paper analyses the research status of sensor networks and several improved LEACH protocols. It is known that there are some shortcomings in current low-energy clustering protocols: the problem of uneven network cluster and unequal energy consumption of each node in the cluster group leads to excessive energy consumption of some nodes, the whole network life cycle is also greatly shortened. This paper proposes a multi-feature fusion energy-saving routing algorithm based on hybrid ant colony algorithm to optimise and upgrade LEACH energy-saving routing model for the internet of things on the basis of LEACH (NPCHS-Leach) to improve the problems of short lifetime and low energy utilisation caused by existing clustering routing protocols, it improves and pro-longs the network life cycle. Finally, the effectiveness of the proposed algorithm is verified by simulation experiments.